Influence of decentralization on structure and dynamics of income and expenditures of local budgets - MARCHUK, Anna (Scientific journal «World of Finance», 2019)
Introduction.The objective reason for the existence of an institution of local budgets is an increase in the efficiency of the provision of public services guaranteed by the state due to the proximity of such services to the immediate consumer. This process is based on the principle of subsidiarity, requires a sufficient level of financial security of local budgets and demonstrates the basic idea of the concept of fiscal decentralization. The decentralization reform is systematic and involves structural changes in various spheres of public life. The object of research of this article is the impact of changes in tax and budget laws aimed at decentralization on structure and dynamics of income and expenditures of local budgets.Purpose.The purpose of the article is to identify trends, priorities and unresolved issues in financing local budget expenditures, compare dynamics of expenditures with dynamics and structural changes in local budget revenues.Results. In the course of the research, the expenditures and revenues of local budgets of Ternopil region during 2004-2017 were analysed, comparison with trends in Ukraine was made. It has been established that due to slowed down economic growth and a systematic decrease in the share of own revenues in recent years, the amount of funding for institutions and activities in the social and cultural sphere has been reduced and the transfer of important functions to the local level was not accompanied by the transfer of sufficient amount of financial resources.Conclusions.The strategic goal of decentralization is to ensure the availability and proper quality of public services for all categories of the population. The decentralized budget system should function on the basis of a coordinated, unified national cooperation policy for many independent institutions, each of which has a legislatively defined sphere of autonomy. Since tax revenues form the main volume of own revenues of local budgets, the issue of improving the efficiency of tax administration comes to the forefront in the context of decentralization changes. Therefore, on the way to ensuring the increase of tax revenues, the strategic goal of local authorities should be to promote economic development of regions.